Utilization of Digital Technology in Improving BPJS Ketenagakerjaan Services - Nazla, Novia; Nurhasanah; Salsabilah, Nurul; Marbun, Patricia; Pahlevi, Habieb; Gurung, Lina; Arisanty , Melisa (Journal of Digital Scholarship in Archives and Information, 2025)
Background of Study: The rapid development of digital technology has encouraged public service institutions like BPJS Ketenagakerjaan to improve their service delivery quality, particularly in response to increasing demands for accessibility and efficiency. Aims and Scope Paper: This study aims to explore how digital technology—particularly applications such as SIPP Online and Jamsostek Mobile (JMO)—has transformed service delivery at BPJS Ketenagakerjaan, especially in underdeveloped and rural areas. Methods: This research employs a descriptive qualitative method, drawing on literature reviews and direct insights gained through internship experience. Data were interpreted thematically based on field observations and analysis of institutional practices. Result: Findings reveal that digital platforms have significantly enhanced user reach, responsiveness, and satisfaction. However, implementation is still hindered by limited digital literacy, infrastructure constraints, and technical issues such as system errors and biometric verification failures. Conclusion: The study underscores the need for continuous digital infrastructure development, user education, and the strengthening of digital ecosystems to ensure inclusive and sustainable service delivery. It offers strategic recommendations to support BPJS Ketenagakerjaan in adopting a user-oriented digital transformation that aligns with data privacy and security standards.